Corpus instructions to medicines as a research method of medical terminology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This paper discusses the current and potential use of corpora in linguistic researches and the role of corpus-based method in analyzing the terminology of medicine in the Ukrainian, Polish and German information leaflets on medicines.
Keywords: medical terminology; text corpus; рatient information leaflet for human medicines